2006
DOI: 10.1007/s11738-006-0003-4
|View full text |Cite
|
Sign up to set email alerts
|

Proline accumulation and real time PCR expression analysis of genes encoding enzymes of proline metabolism in relation to drought tolerance in Andean potato

Abstract: Six potato varieties belonging to four different sub-species were submitted to drought stress during tuberization under controlled field conditions, resulting in contrasting responses of the genotypes to water stress with yield losses varying between 27 and 75%. In all clones free proline accumulated under drought, however, proline levels increased earlier in drought-susceptible varieties than in more tolerant ones. The expression of two key genes in proline metabolism, D 1 -pyrroline-5-carboxylate synthase an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 24 publications
3
37
0
Order By: Relevance
“…Gene products involved in water-deficit responses can be classified into two groups: the first includes proteins, osmolytes, and other compounds that probably confer direct tolerance to abiotic stresses, including chaperones, heat-shock proteins (HSPs), such as HSP70 (Sung et al, 2001), late embryogenesis abundant (LEA) proteins, such as LEA14 (Singh et al, 2002), mRNA-binding proteins, such as glycine-rich protein (Bocca et al, 2005), key enzymes for osmolyte biosynthesis, such as galactinol synthase and delta-1-pyrroline-5-carboxylate synthetase, involved in synthesis of raffinose-family oligosaccharides (Hannah et al, 2006) and proline (Schafleitner et al, 2007), respectively, and water-channel proteins, such as PIP1b (aquaporin; Aharon et al, 2003), which are multi-functional proteins involved in the facilitation of transport of solutes and water in leaves and roots.…”
Section: Introductionmentioning
confidence: 99%
“…Gene products involved in water-deficit responses can be classified into two groups: the first includes proteins, osmolytes, and other compounds that probably confer direct tolerance to abiotic stresses, including chaperones, heat-shock proteins (HSPs), such as HSP70 (Sung et al, 2001), late embryogenesis abundant (LEA) proteins, such as LEA14 (Singh et al, 2002), mRNA-binding proteins, such as glycine-rich protein (Bocca et al, 2005), key enzymes for osmolyte biosynthesis, such as galactinol synthase and delta-1-pyrroline-5-carboxylate synthetase, involved in synthesis of raffinose-family oligosaccharides (Hannah et al, 2006) and proline (Schafleitner et al, 2007), respectively, and water-channel proteins, such as PIP1b (aquaporin; Aharon et al, 2003), which are multi-functional proteins involved in the facilitation of transport of solutes and water in leaves and roots.…”
Section: Introductionmentioning
confidence: 99%
“…Schafleitner et al 27 reported that the expression of both P5CS and PDH did not correlate with the proline levels found in leaf tissue indicating that mechanisms other than transcription participate in the regulation of proline accumulation in potato leaves. Chandra and Dubey 28 reported that although the levels of proline increased with the magnitude of water stress the P5CS activity did not show a corresponding increase in all Cenchrus species which were examined.…”
Section: Discussionmentioning
confidence: 99%
“…Detrimental effects of drought on plants can be observed at the whole-plant level as the death of plants and/or decrease in productivity (Parida and Das, 2005). Drought decreases vegetative potato plant growth (leaves, stems, shoots, and roots) (Ojala et al, 1990;Deblonde and Ledent, 2001), development (Mahajan and Tuteja, 2005;Kar and Kumar, 2007), and production by reducing the number (Eiasu et al, 2007), size (Schafleitner et al, 2007), and quality (Deblonde and Ledent, 2001) of the tubers. Drought stress mainly influences the final potato yield at two stages of potato development, namely tuber initiation and tuber bulking (Martinez et al, 1995).…”
Section: Potato Transcriptomics In Drought and Heat Stressesmentioning
confidence: 99%
“…As an important osmoprotectant, free proline is accumulated more in natural potato plants (Schafleitner et al, 2007), or in transgenic potato plants expressing globe artichoke fructan synthetic pathway genes under drought conditions (Knipp and Honermeier, 2006). Overexpression of P5CS is associated with root development and tolerance against stresses (Taylor, 1996).…”
Section: Transgenics Of Drought and Heat Tolerance In Potatomentioning
confidence: 99%